Single focus on breast magnetic resonance imaging: diagnosis based on kinetic pattern and patient age. (June 2017) - Machida, Youichi; Shimauchi, Akiko; Kuroki, Yoshifumi; Tozaki, Mitsuhiro; Kato, Yoshiaki; Hoshi, Kazuei; Fukuma, Eisuke
Background: Because of its small size, a focus in breast magnetic resonance imaging (MRI) must be evaluated on the basis of characteristics other than morphologic features. Patient-related factors including patient age, in conjunction with lesion-related factors, could be useful for decision-making. Purpose: To assess the probability of malignant foci based on both lesion- and patient-related factors, and to propose a relevant decision-making method. Material and Methods: Foci in our breast MRI database dating from April 2006 to June 2013 were retrospectively identified and analyzed. A Fisher's exact test or a Mann–Whitney U test were performed for univariate analyses, and factors that showed a significant association with outcome in the univariate analyses were subjected to multivariate analysis using a logistic regression model. A decision tree was then drawn using the significant predictors confirmed by multivariate analysis. Results: In total, 184 foci (168 benign, 16 malignant) in 184 patients were analyzed in our study. The presence of a washout pattern and older age were found to be significant predictors of malignancy ( P  < 0.0001; odds ratio [OR], 17.8; P  = 0.021; OR, 1.1, respectively). The main decisive node on the decision tree was the presence of a washout pattern, followed by whether the patient's age was >63 years. Conclusion: An enhancing focus showing a washout pattern, especially in older patients, may warrant immediate biopsy rather than short-interval follow-up.